EDUCATORS AND COLLEGE STUDENTS ABILITY IN ENVIRONMENTAL CARE ATTITUDE - Nelly Yusra; Sakilah; Rian Vebrianto; Yovita; Umar Faruq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimeds to describe the lecturers’ and college students’ ability in environmental care attitude in Pekanbaru. This research is a descriptive qualitative research which was designed through a survey method. The samples were selected using purposive sampling, obtaining 100 people consisting of 16 teachers, 7 lecturers, and 77 students in Pekanbaru. Data were collected through questionnaires and further analyzed based on the Miles and Huberman model including data reduction, data presentation, and conclusion drawing/verification. The results showed that the average score of the environmental care attitude of the lecturers was 90% with a good category. Meanwhile, the average score of the environmental care attitude of the college students was 89.5% in the good category. Thus, it can be concluded that this indicates that educators and students have a good environmental care attitude.